Diagnosis and Treatment Possibilities of Oral Lichen Planus - N. Markovská (Czech Dental Chamber, 2013)
Introduction and aim: The aim of article was description of causes of oral lichen planus a lichenoid lesions on oral mucosal membrane. Oral lichen planus represents most frequently occured chronic of the stratified squamous epithelia. Clinical picture is variable, manifested by basic eflorescence - white polygonal papula, which can form white reticular net till combination of erosion formation. The article presents contemporary division on oral lichen planus, on lichenoid contact reaction, lichenoid medicament's reaction and lichenoid graft reaction versus host reaction. Treatment is paliative and supportive with the aim to decrease pain and clinical signs. The condition of treatment success is to minimalize the bacterial influence, plaque removing, aplication of purposive local antimicrobial teatment and patient education about seriosity of disease. Conclusion: Basic principle of oral lichen planus treatment is early diagnosis, which is completed on analysis of detailed history and on careful examination of oral mucosal membrane. Early diagnosis and early treatment can stop disease on the level of the topical corticoid therapy, whereby it minimize side effects of systematically administrated corticoids in case of advanced oral lichen planus and case of resistant to local corticosteroid. Important part is regular in 3-months interval realised professional oral hygiene and local antibacterial treatment.